The impact of ambient temperature on the spectral characteristics of LED sources in the context of astronomical observations of the night sky - Tabaka, Przemysław; Kołomański, Sylwester (Photonics Letters of Poland, 2024)
The Spectral Power Distribution (SPD) of artificial light sources is a crucial factor in determining the extent of night sky degradation due to light pollution. External temperature affects the properties of LED lamps, including their SPD. In this study, we investigated the impact of ambient temperatures ranging from -25°C to 25°C on the spectral characteristics of 14 LED sources used in outdoor lighting. The obtained SPDs were then used to calculate the Scotopic Sky Luminance Ratio index, enabling the assessment of changes in night sky degradation. Full Text: PDF References K. Baran, A. Różowicz, H. Wachta, S. Różowicz, "Modeling of Selected Lighting Parameters of LED Panel", Energies, 13(14), 3583 (2020). CrossRef P. Tabaka, "Influence of Replacement of Sodium Lamps in Park Luminaires with LED Sources of Different Closest Color Temperature on the Effect of Light Pollution and Energy Efficiency", Energies, 14(19), 6383 (2021). CrossRef P. Tabaka, P. Rozga, "Influence of a Light Source Installed in a Luminaire of Opal Sphere Type on the Effect of Light Pollution", Energies, 13(2), 306 (2020). CrossRef P. Tabaka (ed.), "Sztuczne światło nocą między zagrożeniem a rozwojem", Lodz University of Technology Press (2022), CrossRef D. Sanders, E. Frago, R. Kehoe, Ch. Patterson, K. J. Gaston, "A meta-analysis of biological impacts of artificial light at night", Nature Ecology & Evolution, 5: 74-81 (2021). CrossRef F. Falchi, P. et al., "The new world atlas of artificial night sky brightness", Science Advances, 2, 6 (2016). CrossRef R. F. Green, Ch. B. Luginbuhl, R. J. Wainscoat, D. Duriscoe, "The growing threat of light pollution to ground-based observatories", Astron. Astrophys. Rev., 30, 1 (2022). CrossRef C.C.M. Kyba, "Is light pollution getting better or worse?", Nature Astronomy, 2: 267-269 (2018), CrossRef CIE 2019 "CIE Spectral luminous efficiency for scotopic vision" CrossRef P. Tabaka, S. Kołomański, "Influence of replacing discharge lamps with LED sources in outdoor lighting installations on astronomical observations", Bull. Pol. Acad. Sci. Tech. Sci., 71, 6 (2023). CrossRef M. Deląg, S. Różowicz, A. Różowicz, H. Wachta, "Impact of Ambient Temperature on the Colour Temperature of Low-pressure Mercury Discharge Lamps", Energetyka-Elektryka-Zakłócenia, 12(3) (2021). CrossRef M. Oleksy, J. Kraśniewski, W. Janke, "Wpływ temperatury na charakterystyki optyczne i elektryczne diod LED mocy", Przegląd Elektrotechniczny, 90(9), 83 (2014). CrossRef H. Horvath et al., "Optical characteristics of the aerosol in Spain and Austria and its effect on radiative forcing", J. Geophys. Res., 107, D19 (2002). CrossRef Raport IMGW-PIB DirectLink